Effect of watery extract of Curcuma longa powder (Turmeric) on multidrug- resistant Bacillus cereus recovered from fresh soft cheeses in Kirkuk - Alobaidi, Dahfir (University of Thi-Qar Journal of agricultural research, 2024)
Bacterial contamination is an important cause of foodborne diseases. Herbal medicine is known as botanical medicine or phytomedicine, which means a plant or any part of the plant, is used to prepare medicine to assist in the healing process during illness and disease. Medicinal plants contain natural chemicals, which are acceptable to human and animal systems. Curcumin Is extensively used as an aromatic medicinal cosmetic .It has been in traditional use and it is mentioned as a remedy for various diseases. These findings indicated that action of curcumin had significant inactivation effect on foodborne bacteria, the present study investigate action of curcumin on foodborne bacteria Bacillus cereus (B. cereus).The frequency and distribution pattern of Bacillus cereus in cow soft cheese were investigated indifferent regions in Kirkuk. 50 Pooled soft cheeses samples from different regions in Kirkuk were collected during February until June (2020), ten samples collected monthly from different supermarkets as same as proportion above. Modified procedures for isolation and identification were dependent, Gram stain, oxidase &catalase reaction aid in segregation. Modified Congo red assay used to detect biofilm and Kirby-Bauer disc diffusion method was used for determination sensitivity of isolates to ampicillin (AM 10µg),cephalexin (CLX, 30µg), azithromycin (AZM, 15µ) and vancomycin (VA 30µg). The results confirmed recovery ofIn conclusions. cheese production in Kirkuk are encountered by the problems of bacterial contamination and presence of multidrug resist strain of Bacillus cereus that considered a risk to public health, may be due both insufficient and misuse treatment with antibiotics or in somewhat due to bad quality and/or poor hygiene of processing involved in milk production. Thus recommended monitoring these products for better hygienic status.